Pertumbuhan dan Tingkat Kelangsungan Hidup Ikan Nila (Oreochromis Niloticus) dengan POC NASA dan Tepung Ampas Tahu dalam Pakan - Tamar Mustari (FPIK UNIDAYAN, 2023)
NASA POC is a liquid organic fertilizer that contains macro and micro nutrients, growth regulators and soil microorganisms. Because of this, NASA POC can be used as a raw material for feed to increase fish growth. Another local feed raw material that has high nutritional value and is relatively cheap and easy to obtain is tofu dregs flour. Purposeful research determine the growth and survival of tilapia when using Nasa POC and tofu dregs flour at different doses. This research was conducted for 8 weeks at the FPIK Research Ponds, Dayanu Ikhsanuddin University. The maintenance containers are made of 12 pieces of 18 liter plastic which are equipped with aeration. The test organism used tilapia (Oreochromis niloticus) seeds measuring 5-7 cm and weighing 5-6 grams originating from local fish farming ponds, with a density of 10 fish/container. The study used a completely randomized design with 4 treatments and 3 replications, namely A (0 ml POC Nasa and 0% tofu dregs flour), B (30 ml POC Nasa and 25% tofu dregs flour), C (20 ml POC Nasa and 30% flour tofu dregs), D (10 ml POC Nasa and 35% tofu dregs flour). The results showed that the use of POC Nasa and tofu dregs had an effect on the growth of tilapia (O. niloticus) (P<0.05). The highest absolute growth was in C treatment (20 ml POC Nasa and 30% tofu dregs flour) namely 7.91 ± 0.30 gr, and the lowest was in B treatment (30 ml POC Nasa and 25% tofu dregs flour) namely 6.11 ± 0.15 gr. The highest specific growth (% per day) was in C treatment (20 ml POC Nasa and 30% tofu dregs flour) namely 1.64 ± 0.06, and the lowest was in B treatment (30 ml POC Nasa and 25% tofu dregs flour) namely 1 .38±0.06. The survival rate for all treatments was 100%.